(untitled) (Biological Sciences - PJSIR, 1999)
High termperature stress is a major constraint to increased productivity of cotton in Pakistan. A technique based on physiologicalcharacteristicsisthereforerequiredtoscreenthecultivarsforheat-tolerance.The membranethennostability testconducted onfullygrownyoung leavesofcottonisanappropriatetechniqueforscreeningbreeding material for heat- tolerance.Genotypes testedshowedwidevariationsinadaptationtohightemperaturestressandcouldbebroadly grouped intothreecategoriesonthebasisofcellinjurylevel.Genotypesshowinghighmembranethermostabilitygavehigherseed cotton yield.